PENCIPTAAN KARYA FOTOGRAFI SENI DENGAN TEKNIK LIGHT PAINTING BERGAYA ABSTRAK EKSPRESIONISME: CREATION OF ARTISTIC PHOTOGRAPHY WORKS USING LIGHT PAINTING TECHNIQUE IN ABSTRACT EXPRESSIONISM STYLE - FX Damarjati; Silviana Amanda Aurelia Tahalea (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
Light in photography serves as a fundamental element in capturing objects, with its characteristics influenced by the type of light used. This study explores light experimentation as an artistic subject through a structured fine art photography creation method that emphasizes visual aesthetics. The experiment utilizes artificial light combined with color filters and reflected on various surfaces, both reflective and absorptive. This technique enables an exploration of light-object interactions, creating unique visual effects. The abstract expressionist approach in this experiment positions light as the primary medium in shaping artistic compositions. Through long exposure, light moves freely within the frame, generating dynamic gradients of color, form, and lines. This study aims to introduce new perspectives in fine art photography and contribute to the development of experimental methods in contemporary photography.